Isolation of cytotoxic substance from Kaliapsis sponge - Erna Prawita Setyowati; Umar Anggara Jenie; Sudarsono .; Broto Kardono; Rachmaniar Rahmat; Edy Meiyanto (Indonesian Journal of Pharmacy, 2007)
An isolation of cytotoxic substance of Kaliapsis sponge has been conducted. The substance was isolated using maceration, partition, vacuum liquid chromatography and preparative thin layer chromatograpy methods.The result of research showed that peak 1 has the most cytotoxic activity. Cytotoxicity test with MTT [3 (4,5-dimetiltiazol-2-il)-2,5-difeniltetrazolium bromide] reagen on myeloma cell showed that the peak 1 had a high activity against myeloma cell. It has IC50 equal to 0,18 μg/mL.Key word: Kaliapsis sponge, cytotoxic, myeloma cell